Granular type I corneal dystrophy in a large consanguineous Tunisian family with homozygous p.R124S mutation in the TGFBI gene. (4th July 2019) - Bouyacoub, Yosra; Falfoul, Yousra; Ouederni, Mariem; Sayeb, Marwa; Chedli, Aschraf; Chargui, Mariem; Sassi, Hela; Chakroun Chenguel, Ilhem; Munier, Francis L.; El Matri, Leila; Abdelhak, Sonia; Cheour, Monia
ABSTRACT: Purpose : We report the clinical features and the mutational analysis in a large Tunisian family with granular corneal dystrophy type I (GCD1). Patients and Methods : Thirty-three members of the Tunisian family underwent a complete ophthalmologic examination. DNA extraction and direct Sanger sequencing of the exons 4 and 12 of transforming growth factor β Induced (TGFBI) gene was performed for 42 members. For the molecular modeling of TGFBI protein, we used pGenTHREADER method to identify templates, 3D-EXPRESSO program to align sequences, MODELLER to get a homology model for the FAS1 (fasciclin-like) domains and finally NOMAD-ref web server for the energy minimization. Results : The diagnosis of GCD1 was clinically and genetically confirmed. Sequencing of exon 4 of TGFBI gene revealed the p.[R124S] mutation at heterozygous and homozygous states in patients with different clinical severities. Visual acuity was severely affected in the homozygous patients leading to a first penetrating keratoplasty. Recurrence occurred rapidly, began in the seat of the corneal stitches and remained superficial up to 40 years after the graft. For heterozygous cases, visual acuity ranged from 6/10 to 10/10. Corneal opacities were deeper and predominating in the stromal center. According to bioinformatic analysis, this mutation likely perturbs the protein physicochemical properties and reduces its solubility without structural modification. Conclusions : Our study describes for the first time phenotype-genotype correlation in a large Tunisian family with GCDI and illustrates for the first time clinical and histopathological presentation of homozygous p.[R124S] mutation. These results help to understand pathophysiology of the disease.